2022
DOI: 10.1021/acs.jpclett.2c00693
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Loading on the Water Stability of the Metal–Organic Framework DMOF-1 [Zn(bdc)(dabco)0.5]

Abstract: In this work, the degradation of the metal–organic framework (MOF) DMOF-1 as a function of water adsorption was investigated. As the quantity of water vapor adsorbed by DMOF-1 increases, degradation of the MOF from hydrolysis accelerates. Degradation was attributed to clustering of water molecules in the void space of DMOF-1, as seen in NVT Monte Carlo simulations. Our molecular simulations strongly suggest that degradation of DMOF-1 by water is driven by water adsorption at defect sites in the MOF. Interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…Although these MOFs do not contain free coordination sites for water to readily interact with, they are not stable under >60% relative humidity at RT. Degradation seems to be related to water adsorption at defect sites in the MOFs . Considering water one of the most common contaminants, the possibility of performance in its presence is a relevant parameter for implementation in the current separation industry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these MOFs do not contain free coordination sites for water to readily interact with, they are not stable under >60% relative humidity at RT. Degradation seems to be related to water adsorption at defect sites in the MOFs . Considering water one of the most common contaminants, the possibility of performance in its presence is a relevant parameter for implementation in the current separation industry.…”
Section: Resultsmentioning
confidence: 99%
“…Degradation seems to be related to water adsorption at defect sites in the MOFs. 64 Considering water one of the most common contaminants, the possibility of performance in its presence is a relevant parameter for implementation in the current separation industry.…”
Section: Resultsmentioning
confidence: 99%
“…21 DMOF-1 is of interest because of its unique structure, but it starts to degrade when it comes into contact with water vapor, so it cannot be used in an aqueous phase environment. 22 Second, most MOF materials are made of heavy metal salts, which are expensive and unfavorable for application. For example, the cost of raw materials required for the preparation of zirconium-based MOFs, which are well known for their excellent water stability, is too high, which is the main obstacle to their practical application.…”
Section: Introductionmentioning
confidence: 99%
“…For example, although MOF-5 can adsorb pollutants in water, it does not exist stably in water, leading to its poor reusability . DMOF-1 is of interest because of its unique structure, but it starts to degrade when it comes into contact with water vapor, so it cannot be used in an aqueous phase environment . Second, most MOF materials are made of heavy metal salts, which are expensive and unfavorable for application.…”
Section: Introductionmentioning
confidence: 99%
“…Hossain et al studied the impact of defects on CO 2 and water adsorption in UiO-66 and found that defect sites have a greater influence on low-pressure CO 2 adsorption in MOFs than the coadsorption of water, thus altering the selectivity of the MOF . In a study of water adsorption of DMOF-1 by Chen et al, the presence of defects explained the water intrusion phenomenon observed experimentally . Cai and Sholl showed that point defects in Zn­(tbip) are responsible for the unexpected molecular diffusion behavior in this MOF’s 1D channels and that missing water defects play a pivotal role in the interesting separation phenomena that are possible with the MOF UTSA-280 …”
mentioning
confidence: 99%